2010
DOI: 10.1038/npp.2010.157
|View full text |Cite
|
Sign up to set email alerts
|

How Human Electrophysiology Informs Psychopharmacology: from Bottom-up Driven Processing to Top-Down Control

Abstract: This review surveys human event-related brain potential (ERP) and event-related magnetic field (ERF) approaches to psychopharmacology and psychopathology, and the way in which they complement behavioral studies and other neuroimaging modalities. The major paradigms involving ERP/ERF are P50 suppression, loudness-dependent auditory evoked potential (LDAEP), mismatch negativity (MMN), P300, mental chronometry, inhibitory control, and conflict processing (eg, error-related negativity (ERN)). Together these paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 197 publications
(186 reference statements)
3
67
0
Order By: Relevance
“…However, an important exception was found for P3b latency. The P3b potential reflects target detection and is a cortical correlate of attention to behaviorally relevant stimuli, with latency indicating an upper bound on stimulus classification [Kenemans & K€ ahk€ onen, 2011;Polich, 2007]. Increasing PL is expected to attenuate potentials affected by attention capacity and perceptual demands in accordance with load theory [Lavie, 1995].…”
Section: Top-down Control and Perceptual Capacitymentioning
confidence: 97%
“…However, an important exception was found for P3b latency. The P3b potential reflects target detection and is a cortical correlate of attention to behaviorally relevant stimuli, with latency indicating an upper bound on stimulus classification [Kenemans & K€ ahk€ onen, 2011;Polich, 2007]. Increasing PL is expected to attenuate potentials affected by attention capacity and perceptual demands in accordance with load theory [Lavie, 1995].…”
Section: Top-down Control and Perceptual Capacitymentioning
confidence: 97%
“…50 A number of studies have shown that conflict-or errorrelated evoked potentials are positively modulated by dopaminergic neurotransmission (reviewed in ref. 51 ). There are also reports that these potentials are modulated by a common serotonin transporter polymorphism-to anxiety-related individual differences and clinical phenotypes of anxiety and depression, however, these results have been more mixed.…”
Section: Pharmacology and Animal Modelsmentioning
confidence: 99%
“…Neuropatholological and neuroimaging studies in schizophrenia have shown alterations in DA D 2 receptor (D 2 R) signaling in the striatum, reflected as an elevation both in presynaptic striatal DA synthesis, and density and occupancy of striatal D 2 Rs (Howes and Kapur, 2009), with the latter appearing to be genetically determined in a subpopulation of patients (Allen et al, 2008). Conspicuously, acute challenges with DA augmenting agents have exerted mixed effects on S 1 and S 2 amplitudes and gating (Kenemans and Kähkönen, 2011). Although haloperidol, a D 2 R antagonist, has been shown to normalize amphetamine-induced selective gating deficits in rodents (Stevens and Wear, 1997), treatment of schizophrenia with haloperidol and other conventional or 'typical' antipsychotics has increased S 1 -and S 2 -P50 without improving sensory gating (Freedman et al, 1983;Baker et al, 1987;Adler et al, 1986).…”
mentioning
confidence: 99%